Ageing population, physical activity, and long-term fiscal sustainability: evidence from Poland - Kalbarczyk, Małgorzata; Mackiewicz-Łyziak, Joanna (Studia Demograficzne, 2020)
Our study estimates potential fiscal savings from increased physical activity among older people. This is the first study directly assessing the possible impact of higher physical activity on long-term fiscal sustainability. The study focuses on Poland, where ageing costs are mostly associated with an increase in public spending on healthcare and long-term care. Our results suggest that physical activity has the potential to significantly decrease healthcare and long-term care expenditures. Converting these results into long-term fiscal sustainability, we calculate the S2 indicator, used by the European Commission for the assessment of fiscal sustainability in the long horizon. The long-term component of the indicator, related to ageing costs, is lower by almost 0.7 in comparison with the baseline case, 0.5 of which can be attributed to the reduction in long-term care and 0.2 to the reduction in healthcare. Our results confirm that increased physical activity among older people may lead to a reduction in expenditures related to population ageing and may significantly improve long-term fiscal sustainability.